How space physics really works lessons from well-constructed science fiction - May, Andrew (Springer, 2023)
There is a huge gulf between the real physics of space travel and the way it is commonly portrayed in movies and TV shows. That’s not because space physics is difficult or obscure – most of the details were understood by the end of the 18th century – but because it can often be bafflingly counter-intuitive for a general audience. The purpose of this book isn’t to criticize or debunk popular sci-fi depictions, which can be very entertaining, but to focus on how space physics really works. This is done with the aid of numerous practical illustrations taken from the works of serious science fiction authors – from Jules Verne and Arthur C. Clarke to Larry Niven and Andy Weir – who have taken positive pleasure in getting their scientific facts right
Chapter 1: Physics in Science Fiction ; Chapter 2: Gravity ; Chapter 3: Orbital Dynamics; Chapter 4: Rocket Science ; Chapter 5: Living in a Vacuum
Keywords: bicssc; bisacsh; Physics; Solar system; Gravitation; Astrophysics; Hardcover, Softcover / Physik, Astronomie/Astronomie